Abnormal functional connectivity of high-frequency rhythms in drug-naïve schizophrenia. Issue 1 (January 2018) - Takahashi, Tetsuya; Goto, Takashi; Nobukawa, Sou; Tanaka, Yuji; Kikuchi, Mitsuru; Higashima, Masato; Wada, Yuji
Highlights: We used the phase lag indices of brain networks to study drug-naïve schizophrenia. Schizophrenia led to reduced functional connectivity in high-frequency rhythms. Our results support the dysconnection hypothesis of schizophrenia. Abstract: Objective: The "dysconnection hypothesis" has been proposed as a core neural basis for schizophrenia. Although growing neuroimaging-based evidence suggests atypical functional connectivity in patients with schizophrenia, the results are inconsistent and the effects of antipsychotic treatment remain elusive. Methods: We performed resting-state electroencephalography (EEG) in 21 drug-naïve patients with schizophrenia (14 patients were re-evaluated after administration of antipsychotic treatment) and 31 age-matched healthy control subjects. We estimated functional connectivity, using the phase lag index (PLI), which captures the true synchronization of EEG signals. Results: The patients had reduced functional connectivity of the beta band across frontal regions and of the gamma band throughout the scalp when compared to the control subjects. In the schizophrenia group, symptom severity did not seem associated with functional connectivity. Antipsychotic treatment led to no alterations in functional connectivity. Conclusions: Synchronous activity within and across brain areas over multiple frequencies reflect the integration of various types of information processing. Our findings of abnormal frequency- and region-specific functional connectivity patterns may provide further insight into the "dysconnection hypothesis" of schizophrenia. Significance: The PLI may serve as a useful measure for the characterization and understanding of the intrinsic pathophysiological mechanisms of schizophrenia, and as a reliable biomarker for this disease.